The Lawmaker Role on Concentrations Control: An Analysis of Albanian Market - MoÃ§ka, Ervis; Mehilli, Terida; Demo, Ervin (Mediterranean Journal of Social Sciences, 2012)
This paper' search aims to illustrate: the effectiveness of the legislature on market regulation with objective the economicefficiency' and the context within the â€œAuthority of Competition" implements competition policy. The lawmaker role' on Concentrationscontrol is illustrated through both theoretical and empirical methods of economics and law.The economic analysis shows that, theAlbanian market is a market of small size and there is a risk of the concentration of the market since the demand is limited and operateonly a limited number of companies. We realized that in matters of concentrations with the old Regulation. 4068 of 1989, Albanian lawprovided for only the prohibition of a concentration that creates or strengthens a dominant position, but didn't provided for the abuse thatoccur by this position, as provided by European legislation. In addition, the same regulation didn't give to the Competition Authority thepossibility to take account of technical progress, as the Community Law. In 2008, the Albanian authority, review the provisions of Lawno. 9121 of 28 July 2003 "On Protection of Competition" in order to meet requirements to European competition law under the Europeanintegration process. At the end, the results of the paper, on the effective' market situation in Albania, will be exposed according toeconomic analysis of law.